EB2 promotes hepatocellular carcinoma proliferation and metastasis via MAPK/ERK pathway by modulating microtubule dynamics. Issue 7 (16th April 2021) - Zhong, Fang-Jing; Li, Yi-Ming; Xu, Cong; Sun, Bo; Wang, Ji-Long; Yang, Lian-Yue
Abstract: Metastasis is the main cause of poor postoperative survival of hepatocellular carcinoma (HCC) patients. Cytoskeleton rearrangement is a key event in cancer metastasis. However, the significance of microtubule (MT), one of the core components of cytoskeleton, in this process is only beginning to be revealed. Here, we find that the MT dynamics regulator end-binding protein 2 (EB2) is highly expressed in HCC and predicts poor prognosis of HCC patients. Functional studies show that EB2 overexpression promotes HCC proliferation, invasion and metastasis in vitro and in vivo, while EB2 knockdown has opposite results. Mechanistically, EB2 mediates MTs destabilization, increases Src (Src proto-oncogene non-receptor tyrosine kinase) activity, and thus facilitates extracellular signal-regulated kinase (ERK) signaling activation, which could in turn promote EB2 expression in HCC, eventually resulting in enhanced HCC proliferation, invasion and metastasis. Furthermore, U0126, a specific ERK inhibitor, could effectively inhibit EB2-mediated HCC proliferation and metastasis in vitro and in vivo . In conclusion, EB2 coordinates MT cytoskeleton and intracellular signal transduction, forming an EB2–MT–ERK positive feedback loop, to facilitate HCC proliferation, invasion and metastasis. EB2 could serve as a promising prognostic biomarker and potential therapeutic target for HCC; HCC patients with high EB2 expression may benefit from treatment with ERK inhibitors.